Fluoride Content in Drinking Water of Villages Around Chikhli Dist. Buldana, Maharashtra - Agarkar, S.V. (Asian Journal of Chemistry, 2010)
A survey was carried out to assess the status of fluoride content in drinking water sources of villages around Chikhli town of Buldana District. The drinking water samples were collected from the main sources of water supply of twenty villages around Chikhli. The results clearly indicate that the flouride content in wells, bore wells and hand pumps water is within the permissible limits.